Pengarusutamaan Feminisme di Indonesia: Studi Pemikiran Etin Anwar dan Siti Ruhaini Dzuhayatin - Faridah Amiliyatul Qur'ana; Nur Afina Ulya (Yinyang: Jurnal Studi Islam Gender dan Anak, 2023)
Feminism is an endeavor to incorporate a feminist viewpoint into various organizations and public policies to eliminate gender discrimination in many sectors. This article aims to combine the ideas of two Indonesian Feminism figures: Etin Anwar, an academic who contributes to the thought of Islamic Feminism in Indonesia, and Siti Ruhaini Dzuhayatin, a female activist who fights for women's rights in the Indonesian socio-political context. This study employs descriptive-qualitative approaches to analyze the content of the two figures' thinking work. The findings of this study show that: 1) These two feminist luminaries share comparable perspectives on the growth of feminism in Indonesia. Both advocated for systematic and structural changes to gender equality in order to build an Indonesia society conscious of gender fairness; and 2) Etin Anwar developed the concepts of ethical equality and spiritual equality, as well as further highlighted the five eras of Islamic Feminism construction in Indonesia: emancipation, association, development, integration, and proliferation. At the same time, Siti Ruhaini Dzuhayatin develops the modern organizational concept of gender differentiation, which realizes equality in numerous parts of life. This research is intended to add to Indonesia's understanding and awareness of feminism and feminine issues.